Policy uncertainty and corporate investment: public versus private firms - Christian Dreyer; Oliver Schulz (Review of Managerial Science, 2022)
Using a sample of comparably sized public listed and private firms from nine European countries, we show that public firms reduce their investments by about 50% more than private firms in response to an increase in policy-related uncertainty. We find suggestive evidence that this can be explained by public firms' management being typically subject to greater shareholder scrutiny than private firms' management. Furthermore, only public firms invest more efficiently when confronted with uncertainty. Thus, private firms may benefit from emulating the decision-making processes of public firms in uncertain times.
Keywords: D80; D91; E22; E66; G38; 650; Uncertainty; Investment; Public versus private firms; Shareholder scrutiny